A Survey of Post-Secondary School Deaf Adults Understanding of Mental Health Disorders in Ghana. Issue 5 (3rd September 2022) - Amoako, Samuel; Yankyera, Appiah
ABSTRACT: This study used an online survey to explore the knowledge and understanding of 19 post-secondary school deaf adults on Mental Health Disorders in Ghana. A purposive snowball sampling technique was used to circulate 30 questions online survey to the respondents. An analysis of results showed that most of the deaf participants perceived that evil spirits could cause mental disorders. Also, the participants were optimistic that the conditions of mental disorders could be improved upon through professional medical healthcare access. Furthermore, it was found out that communication barriers, followed by financial difficulty, were the most significant obstacles the deaf participants face in accessing mental health services. Conclusions were drawn and recommendations made based on the study findings.